1. x^4+3x^2-2x+3=x^4+x^3-x^3+3x^2-x^2+x^2-3x+x+3=(x^2-x+1)(x^2+x+3)
2. x^2+4y^2-2x-4y+4xy-35=x^2+4y^2-7x+5x-14y+10y+2xy+2xy=(x+2y-7)(x+2y+5)
3. x^4+2x^3+2x^2+2x+1=x^4+2x^3+x^2+x^2+2x+1=(x^2+2x+1)(x^2+1)=(x+1)^2(x^2+1)
4. a(b+c)² + b(a+c)² + c(a+b)² - 4abc =
= a(b-a+a+c)² + b(a+c)² + c[(a+b)² - 4ab]
= a[(b-a)² + (a+c)² + 2(b-a)(a+c)] + b(c+a)² + c(a-b)²
= a(b-a)² + c(a-b)² + a(a+c)² + b(c+a)² + 2a(b-a)(a+c)
= (b-a)²(a+c) + a(a+c)² + b(a+c)² + 2a(b-a)(a+c)
= (a+c)[(b-a)² + a(a+c) + b(a+c) + 2a(b-a)]
= (a+c)(b² + a² - 2ab + a² + ac + ab + bc + 2ab - 2a²)
= (a+c)(b² + bc + ac + ab)
= (a+c)[b(b+c) + a(c+b)]
= (a+c)(b+c)(b+a)
5. phải là cộng 2abc mới đúng bạn ạ
ab(a+b)-bc(b+c)+ac(c+a)+2abc
= a^2b + ab^2 + b^2c + bc^2 + ca(c+a) + 2abc
= ab^2 + b^2c + a^2b + bc^2 + 2abc + ca(c+a)
= b^2(a+c) + b(a^2 + c^2 + 2ac) + ca(c+a)
= b^2(a+c) + b(a+c)^2 + ca(c+a)
= (c+a)[b^2 + b(a+c) + ca]
= (c+a)[b^2 + ab + bc + ca]
= (c+a)[b(b+a) + c(b+a)]
= (c+a)(b+c)(b+a)